Novel Usher syndrome pathogenic variants identified in cases with hearing and vision loss - Justin A. Pater; Jane Green; Darren D. O'Rielly; Anne Griffin; Jessica Squires; Taylor Burt; Sara Fernandez; Bridget Fernandez; Jim Houston; Jiayi Zhou; Nicole M. Roslin; Terry-Lynn Young (BMC, 2019)
Abstract Background Usher syndrome, the most common form of inherited deaf-blindness, is unlike many other forms of syndromic hereditary hearing loss in that the extra aural clinical manifestations are also detrimental to communication. Usher syndrome patients with early onset deafness also experience vision loss due to progressive retinitis pigmentosa that can lead to legal blindness in their third or fourth decade. Methods Using a multi-omic approach, we identified three novel pathogenic variants in two Usher syndrome genes (USH2A and ADGRV1) in cases initially referred for isolated vision or hearing loss. Results In a multiplex hearing loss family, two affected sisters, the product of a second cousin union, are homozygous for a novel nonsense pathogenic variant in ADGRV1 (c.17062C > T, p.Arg5688*), predicted to create a premature stop codon near the N-terminus of ADGRV1. Ophthalmological examination of the sisters confirmed typical retinitis pigmentosa and prompted a corrected Usher syndrome diagnosis. In an unrelated clinical case, a child with hearing loss tested positive for two novel USH2A splicing variants (c.5777-1G > A, p. Glu1926_Ala1952del and c.10388-2A > G, p.Asp3463Alafs*6) and RNA studies confirmed that both pathogenic variants cause splicing errors. Interestingly, these same USH2A variants are also identified in another family with vision loss where subsequent clinical follow-up confirmed pre-existing hearing loss since early childhood, eventually resulting in a reassigned diagnosis of Usher syndrome. Conclusion These findings provide empirical evidence to increase Usher syndrome surveillance of at-risk children. Given that novel antisense oligonucleotide therapies have been shown to rescue retinal degeneration caused by USH2A splicing pathogenic variants, these solved USH2A patients may now be eligible to be enrolled in therapeutic trials.